Changes in Cardiovascular Health, Genetic Risk, and Cardiometabolic Diseases: Evidence From a Large‐Scale Cohort Study - Shuaizhou Chen; Jialin Li; Qiuhong Man; Chengxin Hu; Jinchen Li; Jianwei Wang; Siyu Wu; Kelin Xu; Mei Cui; Tiejun Zhang; Xingdong Chen; Chen Suo; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Evidence has firmly established the association between superior cardiovascular health (CVH) and reduced susceptibility to cardiometabolic diseases (CMDs). In reality, CVH experiences dynamic fluctuations throughout individuals' lifespans. However, the association between changes in CVH and the impact on CMDs among individuals with different genetic risks remains unclear. Methods and Results Based on a large‐scale community‐based cohort, we evaluated the association between baseline CVH (n=289 069), changes in CVH between 2 examinations (n=37 702), and the risk of CMDs and its individual components (ischemic heart disease, type 2 diabetes, and stroke) using Cox proportional hazards models, leveraging detailed repeatedly assessed lifestyle information and genetic data. Estimations were also stratified by age groups (≤65 years, >65 years) and genetic risk groups, defined by the tertiles of the polygenic risk score for CMDs components. Population‐attributable fractions and relative risk reduction were calculated to assess the potential benefits of improvement in CVH in preventing CMDs. For participants whose baseline CVH ranged from ideal to poor, an ascending trend was exhibited in the risk of CMDs overall, as well as its individual components. Based on a median of 5.4‐year follow‐up after the reassessment of CVH, individuals with an enhancement from intermediate to ideal CVH demonstrated a 36% lower risk of CMDs (hazard ratio [HR], 0.64 [95% CI, 0.53–0.77]; P<0.001), compared with those with constantly intermediate CVH, while those deteriorating from intermediate to poor faced a 44% higher risk (HR, 1.44 [95% CI, 1.17–1.78]; P<0.001). Interestingly, changes in CVH exerted a more pronounced impact on CMD risk within younger populations (≤65 years) (Pinteraction=0.006). Notably, among participants with a high genetic risk of ischemic heart disease, those who improved their CVH status from intermediate to ideal exhibited a 50% lower risk of ischemic heart disease (HR, 0.50 [95% CI, 0.34–0.74]; P<0.001), compared with those with constantly intermediate CVH. Conclusions Individuals with better baseline CVH exhibited a lower risk of CMDs. Enhancement in CVH significantly mitigates the risk of CMDs, especially when efforts are made before the age of 65 years and within high genetic risk groups. These findings underscore the importance of interventions aimed at promoting cardiovascular well‐being across entire populations, offering valuable insights for targeted preventive strategies and healthcare interventions.